First phylogenetic analysis of the Miocene armadillo Vetelia reveals novel affinities with Tolypeutinae - Barasoain Goñi, Daniel (2021)
Vetelia is a Miocene genus of armadillos from Argentina and Chile, traditionally included within the subfamily Euphrac tinae (Chlamyphoridae, Cingulata, Xenarthra). It includes the species Vetelia puncta (early?middle Miocene), Vetelia perforata (middle?late Miocene), and Vetelia gandhii (late Miocene), mostly known by isolated osteoderms. In this con tribution, we provide the first description of the skull for this genus, based on new materials (PVSJ289 and PVSJ154) here assigned to V. gandhii. A detailed characterization allows us to amend the diagnosis of the three known species, and to include, for the first time, the genus Vetelia into a morphological phylogenetic analysis. Phylogenetic results reveal a closer affinity to the Tolypeutinae, including the extant genera Priodontes (giant armadillos), Cabassous (nakedtailed armadillos), and Tolypeutes (three banded armadillos), and the fossil genera Pedrolypeutes and Kuntinaru, than to the Euphractinae. More specifically, Vetelia is included within the Priodontini, as sister group of the clade composed by Cabassous + Priodontes. Taking into account the scarce record of fossil Tolypeutinae, this new proposal fills an impor tant temporal gap in the evolutionary history of this linage. Finally, we also provide new information on the diagnostic morphological characters of the Priodontini and Tolypeutini.